Early Detection of Susceptibility to Acute Lung Inflammation by Molecular Imaging in Mice Exposed to Cigarette Smoke - Sandra Pérez-Rial; Laura del Puerto-Nevado; Nicolás González-Mangado; Germán Peces-Barba (Molecular Imaging)
Matrix metalloproteinases (MMPs) are extracellular proteolytic enzymes involved in acute lung inflammation in response to cigarette smoke exposure (CSE). We present the in vivo detection of MMP activity using a specific MMP-activatable, near-infrared, polymer-based proteolytic probe in strains of mice with different susceptibility to developing smoking-induced emphysema (susceptible mice, C57BL/6j, and resistant mice, 129S2/SvHsd) to characterize the distinctive profile of CSE-induced acute inflammation. In vivo imaging of pulmonary inflammation expressing MMPs revealed a significantly different median ratio twofold higher in smoker than in nonsmoker susceptible mice (C57BL/6j) and no significant differences between the smoker and the nonsmoker group in resistant mice (129S2/SvHsd). Ex vivo imaging of the lungs of each group of mice confirmed the same in vivo experiment results obtained for both strains of mice. In the biochemical study of lung tissue, the proteolytic signal colocalized with the endogenously expressed MMP protein levels, with MMP-9 levels that are 2.2 times higher than in the nonsmoke-exposed group in C57BL/6j mice and no significant differences in the 129S2/SvHsd mice. The MMP-activatable probe provides a useful reagent for the in vivo and ex vivo detection of MMP-selective proteolytic activity. We are able to distinguish between susceptible and resistant strains of mice in terms of the profile of MMP activity in the early stages of pulmonary disease.